Consumer Protection Against Buying and Selling Transactions of Mobile Legends Diamonds on Instagram Platform - Hutabarat, Josefid Keitharo; Andriyanto Adhi Nugroho (Dinasti Research, 2024)
The high number of players in a game can be leveraged by certain individuals to make a profit. In games, there are digital items that can be bought and sold. For example, in the game Mobile Legends, there is something called diamonds. Besides being able to be purchased through Mobile Legends, diamonds are also widely sold in stores opened on Instagram. As its function, Instagram is a social media platform. Unlike Tokopedia or Shopee, which are E-Commerce platforms, Instagram does not have any responsibility for buying and selling activities that occur on its platform. This makes purchases through stores on Instagram more vulnerable to crimes such as fraud. Therefore, the existence of the Consumer Protection Law and ITE Law serves as protection for consumers who wish to engage in buying and selling transactions on social media platforms. This research used a normative juridical research method, wherein law served as the primary guide to examine theories and cases related to this study. The author used two approaches in conducting this research: the statutory approach and the case approach. The results of this study aimed to reveal that legal protection for consumers is regulated by consumer protection laws, thereby necessitating businesses to provide it to consumers.